Retirement Income Policy and National Savings - David Law (New Zealand Government, The Treasury, 2013)
This paper examines the implications for national savings of three retirement income policy options, designed to improve the fiscal sustainability of New Zealand Superannuation (NZS). A simple model is developed that employs population and longevity projections allowing estimation of the contributions that many overlapping age cohorts might make to national savings in response to policy change. Government contributions to national savings, resulting primarily from reduced NZS payments, are also considered. Results suggest that even seemingly modest changes to retirement income policies could lead to substantial cumulative changes in national savings by 2061.
Keywords: E21; D10; D91; 330; National Savings; Household Saving; Fiscal Saving; Retirement Income; New Zealand Superannuation; New Zealand